Investigations of Dual Plug Argon Blowing for Efficient Mixing at Ladle Furnace Station - M. Warzecha; A. Hutny; P. Warzecha; Z. Kutyła; T. Merder (Archives of Metallurgy and Materials, 2021)
The article presents the results of model research concerning the change of technology of argon blowing into liquid steel at the ladle furnace, using the dual plug system. The results of numerical simulations were verified with experimental data carried out on the water model device. The verified model was used to perform numerical simulations to predict the impact of using a new gas injection technology – with different flow rates – on the time to achieve the assumed degree of metal chemical homogenization after alloy addition. Simulation results show that argon blowing metal bath in dual plug mode can effectively reduce mixing time compared to conventional technology with the same gas flow rates. Generally, the use of the dual plug system is beneficial for reducing the bath mixing time, however, the assumed optimal proportion of gas blown through individual plug should be followed. Finally, numerical predictions were used to perform experimental melt under industrial conditions. Industrial verification has clearly confirmed the validity of numerical modeling and showed that also in industrial conditions, a shorter time of chemical homogenization was obtained for the dual plug system.